A salivary GMC oxidoreductase of Manduca sexta re-arranges the green leaf volatile profile of its host plant - Lin, Yu-Hsien; Silven, Juliette J M; Wybouw, Nicky; Fandino, Richard A; Dekker, Henk L; Vogel, Heiko; Wu, Yueh-Lung; de Koster, Chris; Große-Wilde, Ewald; Haring, Michel A; Schuurink, Robert C; Allmann, Silke (Nature communications, 2023)
Green leaf volatiles (GLVs) are short-chain oxylipins that are emitted from plants in response to stress. Previous studies have shown that oral secretions (OS) of the tobacco hornworm Manduca sexta, introduced into plant wounds during feeding, catalyze the re-arrangement of GLVs from Z-3- to E-2-isomers. This change in the volatile signal however is bittersweet for the insect as it can be used by their natural enemies, as a prey location cue. Here we show that (3Z):(2E)-hexenal isomerase (Hi-1) in M. sexta's OS catalyzes the conversion of the GLV Z-3-hexenal to E-2-hexenal. Hi-1 mutants that were raised on a GLV-free diet showed developmental disorders, indicating that Hi-1 also metabolizes other substrates important for the insect's development. Phylogenetic analysis placed Hi-1 within the GMCβ-subfamily and showed that Hi-1 homologs from other lepidopterans could catalyze similar reactions. Our results indicate that Hi-1 not only modulates the plant's GLV-bouquet but also functions in insect development.
Keywords: Animals; Phylogeny; Catalysis; Body Fluids; katalýza; zvířata; fylogeneze; Plant Leaves; Manduca; listy rostlin; tělesné tekutiny